Clinical Characteristics and Relevance of Dizziness in Patients with de novo Parkinson’s Disease - Kyum-Yil Kwon; Jihwan You; Rae On Kim; Eun Ji Lee (Journal of Integrative Neuroscience, 2024)
Background: The purpose of this study was to determine the detailed characteristics of dizziness in patients with de novo Parkinson’s disease (PD) and the clinical implications of dizziness. Methods: Ninety-three people with de novo PD were enrolled between July 2017 and August 2022 for this retrospective study. Using each representative scale, various motor and non-motor symptoms were assessed. In addition, clinical manifestations of dizziness in those patients, including its presence, type, frequency, and duration of occurrence, were investigated. Results: Thirty-nine patients with de novo PD reported dizziness, with presyncope being the most common (38%). The most common frequency was several times a week (51%). The most common duration was a few seconds (67%). Multivariable logistic regression analysis showed that dizziness was more common in women than in men {odds ratio (OR): 3.3601, 95% confidence interval (CI): 1.0820–10.4351, p = 0.0361}. Dizziness was significantly related to non-motor symptoms of low global cognition (OR: 0.8372, 95% CI: 0.7285–0.9622, p = 0.0123) and severe autonomic dysfunction (OR: 1.1112, 95% CI: 1.0297–1.1991, p = 0.0067). A post-hoc analysis revealed that dizziness was only associated with cardiovascular dysautonomia (adjusted OR: 10.2377, 95% CI: 3.3053–31.7098, p < 0.0001) among several domains of dysautonomia. Conclusions: About 42% of patients with de novo PD complained of dizziness. The occurrence of dizziness in those people was highly associated with female gender women, cognitive impairment, and cardiovascular dysautonomia. These results suggest that clinicians should pay close attention when patients with PD complain of dizziness.